Answer:
d x 7 = 105
Step-by-step explanation:
<u>Given </u><u>:</u><u>-</u><u> </u>
<u>To </u><u>Find</u><u> </u><u>:</u><u>-</u><u> </u>
- To find the factorised form .
<u>Answer</u><u> </u><u>:</u><u>-</u><u> </u>
Taking the given expression,
→ 4x² - 8x + 4
→ 4x² - 4x -4x + 4
→ 4x ( x - 1 ) -4( x -1)
→ (4x - 4)(x-1)
<u>Hence </u><u>the</u><u> </u><u>required</u><u> answer</u><u> is</u><u> </u><u>(</u><u>4</u><u>x</u><u> </u><u>-</u><u> </u><u>4</u><u>)</u><u>(</u><u> </u><u>x </u><u>-</u><u> </u><u>1</u><u>)</u><u> </u><u>.</u>
Answer:
28.3
Step-by-step explanation:
12/20 = 17/x
cross multiply
12x=340
divide each side by 12
x=28.3333333333.......
round it to nearest tenth
28.3
Answer: (-1, -2) or (-2, 1)
Step-by-step explanation:
i graphed it on desmos and used the intersected points.
Answer: 2 1/3
Explanation:
10 2/6 - 7 5/6
You can make both a fraction by multiplying the denominator by the whole number, and then adding the numerator to that number, and keeping the denominator the same. So, 10*6 = 60 and 60 + 2 = 62 and you keep the denominator as 6, which would make 62/6
7*6 = 42 and 42 + 5 = 47 so 7 5/6 becomes 47/6
10 2/6 is equivalent to 62/6
7 5/6 is equivalent to 47/6
This just makes it easier to look at.
Now you just work through the equation.
62/6 - 47/6 = 15/6
15/6 = 2 3/6 = 2 1/3